Clinical, Laboratory, and Electrocardiographic Findings in Colchicine Toxicity: 10 Years of Experience - Sheibani, Mehdi; Zamani, Nasim; Gerami, Amir Hushang; Akhondi, Hossein; Hassanian-Moghaddam, Hossein (Frontiers in Medicine, 2022)
Background: We aimed to investigate the clinical, laboratory, and electrocardiographic (ECG) findings of colchicine poisoning and to evaluate if there is a correlation between them and the two major outcomes of this toxicity which are respiratory/cardiovascular failure and death. Materials and Methods Medical records of 34 colchicine-intoxicated patients that were treated in our center during the past 10 years were retrospectively evaluated. The patient's clinical presentation, vital signs, laboratory tests, ECGs, and outcomes were reviewed. Results Abdominal pain, and hypotension at presentation had significant correlation with mortality (p = 0.003, OR: 2.2 [4.1, 7.9], p = 0.029, OR: 13.0 [1.5, 111.8]). Mortality significantly occurred in those with sinus tachycardia, hypokalemia, metabolic acidosis, and impaired liver and kidney function tests (p-values = 0.025, 0.007, 0.04, and 0.008, respectively). All the patients had some ECG abnormalities. Most frequent ECG abnormalities were pathologic ST segment elevation and depression (70%), left atrial enlargement (48%), and sinus tachycardia (37%), PR elevation in aVR lead (37%), and T wave inversion (37%). Conclusions Colchicine toxicity is a dangerous entity regarding the cardiovascular events and requires close general and cardiac monitoring.